GAMBARAN SISTEM MANAJEMEN LIMBAH ARSIP BAHAN BERBAHAYA DAN BERACUN (B3) DI RUMAH SAKIT JIWA MUTIARA SUKMA MATARAM - Virnaz Permata Ayu; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
The B3 waste sorting process at Mutiara Sukma Mental Hospital has been carried out in a structured manner in each service unit with separation according to biohazard type and standards, under the supervision of the Waste Management Team, although there are still inconsistencies in some units that require increased supervision and training. B3 waste storage is carried out in a special room with a maximum time of 2 x 24 hours in accordance with the provisions of the Minister of Health Regulation and Government Regulation, but still requires technical improvements such as ventilation, room temperature, and protective equipment. Waste transportation and destruction are in collaboration with a third party licensed by the Ministry of Environment and Forestry and are equipped with manifest documents, but staff understanding regarding the documentation flow and handover procedures still needs to be improved through internal socialization.